2016
DOI: 10.11648/j.ijber.20160504.12
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Conservatism Alleviates Firm’s Investment Efficiency: An Evidence from China

Abstract: Abstract:This study examined the association of accounting conservatism with investment efficiency, and its effects on investment efficiency by mitigating firms from under and over investments of listed companies in China (2002China ( to 2013. First, we find the existence of conservatism in accounting practices of Chinese firms, later to hypothesize that how conservatism improves investment efficiency to alleviate under or over investment stresses. Thus, our findings confirmed that accounting conservatism imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
2
6
0
2
Order By: Relevance
“…This result agrees with the findings of prior literature that found that accounting conservatism reduced cost of debt and facilitated debt contracting process (Karthik, Watts and Zuo, 2016;Razzaq, Riu and Donghua, 2016;Lara, Osma and Penalva, 2016;Hong, Kim andLobo, 2017, Yasir, 2018). However, this result contradicts with other studies which found that conservatism might discourage managers to invest in high risk projects even with a positive net present value (Liu, 2014;Brockman, Liu and Ma, 2015;Ashfaq et al, 2016).…”
Section: Discussion Of the Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…This result agrees with the findings of prior literature that found that accounting conservatism reduced cost of debt and facilitated debt contracting process (Karthik, Watts and Zuo, 2016;Razzaq, Riu and Donghua, 2016;Lara, Osma and Penalva, 2016;Hong, Kim andLobo, 2017, Yasir, 2018). However, this result contradicts with other studies which found that conservatism might discourage managers to invest in high risk projects even with a positive net present value (Liu, 2014;Brockman, Liu and Ma, 2015;Ashfaq et al, 2016).…”
Section: Discussion Of the Findingssupporting
confidence: 92%
“…Thereby, conditional conservatism was considered an efficient mechanism in controlling and monitoring the opportunistic behavior of managers. Razzaq, Riu and Donghua (2016) indicated that there was a positive cone1ation between accounting conservatism and investment efficiency. Accounting conservatism reduces overinvestment problem through monitoring managers' decisions and decreasing free cash flow available for them.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior academic reported that conditional accounting conservatism is caused to lowers the cost of capital researchers (Francis & Martin, 2010). Most recent researchers studied that accounting conservatism has influenced on the cost of capital and their outcomes showed that accounting conservatism decreases the cost of capital (Lambert et al, 2007;Lara et al, 2009b;Razzaq, Rui, & Donghua, 2016). Therefore, current paper advances a postulate that conservative financial reporting lessens the cost of capital for the companies in emerging market.…”
Section: Hypothesis Developmentmentioning
confidence: 80%
“…Penelitian tentang pengaruh spesialisasi auditor terhadap efisiensi investasi banyak dilakukan namun inkonsistensi hasil penelitian masih ditemukan, menurut (Elaoud & Jarboui, 2017) dalam penelitiannya menyatakan bahwa Spesialisasi auditor membantu menekan tingkat underinvestment pada perusahaan. Penelitian tentang konservatisme akuntansi sudah banyak diteliti namun masih adanya inkonsistensi hasil yang ditemukan oleh (Lara et al, 2016) menyatakan bahwa konservatisme akuntansi dapat meningkatkan efisiensi investasi dan tingkat hutang karena kemudahan pengawasan manajer, selanjutnya penelitian yang dilakukan oleh (Juliani & Wardhani, 2018) menyatakan bahwa konservatisme akuntansi berpengaruh positif terhadap efisiensi investasi, dalam penelitian (Razzaq et al, 2016) menyatakan bahwa Konservatisme akuntansi meningkatkan efisiensi investasi perusahaan China dengan mengurangi Overinvestment dan Underinvestment, berbeda dengan penelitian (Houcine, 2013) yang menyatakan bahwa Konservatisme tidak mempengaruhi efisiensi investasi pada perusahaan di Tunisia karena pengaruh perbedaan dasar hukum dengan Amerika. Selain konservatisme, kualitas laporan keuangan juga mempengaruhi efisiensi investasi, penelitian tentang kualitas laporan keuangan ini sudah banyak dilakukan namun masih adanya inkonsistensi dalam penelitian ini.…”
Section: Info Artikel Abstrak Sejarah Artikelunclassified